Explaining divergent transformation paths in Tunisia and Egypt: The role of inter-elite trust. Issue 5 (19th October 2020) - Hassan, Mazen; Lorch, Jasmin; Ranko, Annette
ABSTRACT: This article analyses why the political transformations following the Arab Spring took different paths in Egypt and Tunisia. Based on data from field interviews conducted between 2012 and 2018 as well as press analyses, we argue that a strong factor why Tunisia was more successful in establishing democracy is that it had a higher level of inter-elite trust. Moreover, we show that the establishment of inter-elite trust depends on the presence of functioning trust-building arenas during the transition and the early democratic consolidation period. To investigate the role of inter-elite trust, we develop a theoretical-analytical framework, drawing on Arab Spring literature, transition theory, scholarship on democratic consolidation, and research on trust.